Global shape perception contributes to crossmodal correspondences - Chen, YC; Huang, P; Spence, CJ (American Psychological Association, 2021)
The Bouba/Kiki effect constitutes a classic sound-shape correspondence, with the meaningless sounds “Bouba” and “Kiki” being mapped onto smooth and spiky patterns, respectively. While it is commonly believed that the Bouba/Kiki effect is driven by the local rounded and angular features of a pattern, here we investigated the importance of an alternative level of visual processing— namely the global contours. We adopted compound radial frequency (RF) patterns and segmented them into convexities (outward curves) or concavities (inward curves). Note that convexities are more informative in terms of inferring the global contour than concavities. When the perceptual grouping of segments was facilitated by increasing their length, the grouping of convexities was more efficient than that of concavities as manifested by the closer matching judgments to the compound RF patterns. When we interfered with the perceptual grouping of segments by rotating each segment by 180º, the matching consensus of convexities was higher when they were presented in the original than in the reversed orientation. Hence, the Bouba/Kiki effect was susceptible to the factors modulating the perceptual grouping process going from segments to the global contour, suggesting that the Bouba/Kiki effect may occur at the global level of shape perception. Sound shape correspondences would therefore seem to be expressed at multiple levels of information processing, furthering our understanding of the development, underpinning neural mechanisms, and applications of crossmodal correspondences.